A high content clonogenic survival drug screening identifies maytansine as a potent radiosensitizer for meningiomas - Yu, Jinxiu; Deng, Jiaojiao; Ren, Leihao; Hua, Lingyang; Wu, Tianqi; Hui, Yi; Shao, Chunlin; Gong, Ye (Frontiers in Immunology, 2025)
PurposeRadiation resistance significantly hinders the efficacy of radiotherapy for meningiomas, posing a primary obstacle. The clinical inadequacy of therapeutic drugs and radiosensitizers for treating meningiomas further exacerbates the challenge. Therefore, the aim of this study was to identify potential radiosensitizers for treating meningiomas.MethodsA high content clonogenic survival drug screening was employed to evaluate 166 FDA-approved compounds across varied concentration ranges. Cell viability, apoptosis, and radiosensitization were assessed using CCK-8 assays, Annexin V-FITC/PI assays and standard colony formation assays. Transcriptome sequencing, immunofluorescence and cell cycle experiments were conducted to assess transcriptional profile, DNA double-strand break damage and cell cycle distribution. Finally, the radiosensitizing effect of Maytansine was assessed in vivo through subcutaneous tumor implantation in nude mice.ResultsThe proportion of maytansine exhibiting SRF≥1.5 within the detectable concentration range was 100%. CCK-8 assay indicated the IC50 values of maytansine for IOMM-Lee and CH157 were 0.26 ± 0.06 nM and 0.31 ± 0.01 nM, respectively. Standard clonogenic survival assays and Annexin V-FITC/PI assays revealed maytansine had a notable radiosensitizing effect on meningioma cells. Transcriptome sequencing analysis demonstrated that maytansine can modulate cell cycle and DNA damage repair. Immunofluorescence analysis of γ-H2AX and cell cycle experiments demonstrated that Maytansine enhances DNA double-strand breaks and induces G2/M phase arrest. Moreover, in vivo studies had indicated that Maytansine augments the therapeutic efficacy of radiotherapy.ConclusionThis study highlighted the potential of maytansine as a potent inhibitor and radiosensitizer for meningiomas by inducing G2/M phase cell cycle arrest and enhancing DNA double-strand break damage. These findings opened up a promising path in the development of radiosensitizers aimed at treating this condition.